An Improved BS_NAHOSM Hybrid Control Strategy for FOC of Dual Star Induction Motor Drives - Pham, Ngoc Thuy (Periodica polytechnica. Electrical engineering and computer science, 2025)
In this paper, a novel adaptive hybrid control structure for field-oriented control (FOC) of six-phase induction motor (SPIM) drives is proposed. The controller effectively integrates backstepping (BS) control for the outer loops with a novel adaptive higher-order sliding mode (NAHOSM) controller for the inner current loop. This control strategy also proposes load disturbance estimator using a predictive model to estimate the component required for the BS_NAHOSM control strategy to help identify and proactively eliminate disturbances. The proposed approach demonstrates robust and stable performance under parameter uncertainties and load disturbances, while significantly reducing the chattering phenomenon. Simulation results obtained using MATLAB/Simulink confirm the effectiveness and superiority of the proposed control strategy.